Cryolipolysis for Fat Reduction and Body Contouring: Safety and Efficacy of Current Treatment Paradigms. Issue 6 (June 2015) - Ingargiola, Michael J.; Motakef, Saba; Chung, Michael T.; Vasconez, Henry C.; Sasaki, Gordon H.
Abstract : Background: Cryolipolysis is a nonsurgical technique for localized fat reduction. With the increased risk of complications from more invasive methods such as liposuction, cryolipolysis presents a promising method for nonsurgical body contouring. This study presents a systematic review of the available clinical data, with an emphasis on the efficacy, methods, safety, and complications of cryolipolysis. Methods: To identify clinical studies that assessed outcomes of cryolipolysis, a systematic review of the MEDLINE and Cochrane databases was performed with the search algorithm cryolipolysis OR cool sculpting OR fat freezing OR lipocryolysis. Results: The primary literature search returned 319 articles. After inclusion criteria were applied and additional articles were idenfied via manual review of article references, 19 studies were selected for review. Average reduction in caliper measurement ranged from 14.67 percent to 28.5 percent. Average reduction by ultrasound ranged from 10.3 percent to 25.5 percent. No significant impact on lipid levels or liver function tests after cryolipolysis treatments was noted in any study. Only mild, short-term side effects, such as erythema, swelling, and pain, were noted. Paradoxical adipose hyperplasia was described in one patient. Conclusions: Cryolipolysis is a promising procedure for nonsurgical fat reduction and body contouring and presents a compelling alternative to liposuction and other, more invasive methods. This procedure appears to be safe in the short term, with a limited side effect profile, and results in significant fat reduction when used for localized adiposities. It remains unclear whether posttreatment manual massage and multiple treatments in the same anatomic area enhance the efficacy of cryolipolysis.